Rheological Characteristics of Tire Rubber-Modified Asphalt following Thermal Variation - S. Chen; J. Cao; C. f. Zheng; X. D. Guo (Geofluids)
In recent years, due to the development of the automobile industry, there are more and more waste car tires, and the reuse of waste tires has become an urgent problem to be solved. In this study, the crushed rubber of waste automobile tires is used to modify asphalt to prepare rubber-modified asphalt, which can not only solve the problem of using waste tires but also effectively improve the performance of asphalt pavement. This study defines four modified asphalts with different rubber powder content, which are defined as 1#, 2#, 3#, and 4#, respectively. The performance difference between the four modified asphalts and the base asphalt was compared through experiments to illustrate the advantages of rubber-modified asphalt. The four selected rubber asphalts and base asphalt are subjected to the viscous toughness test, apparent viscosity test, DSR test, and BBR test to determine the high- and low-temperature characteristics of rubber asphalt. The analysis of experimental data shows that rubber-modified asphalt can effectively improve the low-temperature performance of the asphalt, make the asphalt have better toughness, and also improve the high-temperature shear resistance of the asphalt. Finally, it is determined that adding 10% rubber powder to the base asphalt has the best effect.